E-cigarettes for the management of nicotine addiction - Knight-West O; Bullen C (Dove Medical Press, 2016)
Oliver Knight-West, Christopher Bullen The National Institute for Health Innovation, School of Population Health, The University of Auckland, Auckland, New Zealand Abstract: In this review, we discuss current evidence on electronic cigarettes (ECs), a rapidly evolving class of nicotine delivery system, and their role in managing nicotine addiction, specifically in helping smokers to quit smoking and/or reduce the amount of tobacco they smoke. The current evidence base is limited to three randomized trials (only one compares ECs with nicotine replacement therapy) and a growing number of EC user surveys (n=6), case reports (n=4), and cohort studies (n=8). Collectively, these studies suggest modest cessation efficacy and a few adverse effects, at least with the short-term use. On this basis, we provide advice for health care providers on providing balanced information for patients who enquire about ECs. More research, specifically well-conducted large efficacy trials comparing ECs with standard smoking cessation management (eg, nicotine replacement therapy plus behavioral support) and long-term prospective studies for adverse events, are urgently needed to fill critical knowledge gaps on these products. Keywords: tobacco, smoking, nicotine, electronic cigarettes, cessation, addiction